2021
DOI: 10.1186/s12889-021-11231-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perceptions of Alzheimer’s disease in three ethnic groups of younger adults in the United Kingdom

Abstract: Background Alzheimer’s disease (AD) is a global public health problem with an ageing population. Knowledge is essential to promote early awareness, diagnosis and treatment of AD symptoms. AD knowledge is influenced by many cultural factors including cultural beliefs, attitudes and language barriers. This study aims: (1) to define AD knowledge level and perceptions amongst adults between 18 and 49 years of age in the UK; (2) to compare knowledge and perceptions of AD among three main ethnic grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
0
6
0
2
Order By: Relevance
“…In our study, young people's knowledge level about dementia was 63.5%, which was higher than the relevant study. 22 On the other hand, young and older female groups had very close mean scores. This result may be related to the fact that women are more likely to be caregivers in each period of life and the majority of women assume the primary responsibility for any illness and care in their family in the society.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, young people's knowledge level about dementia was 63.5%, which was higher than the relevant study. 22 On the other hand, young and older female groups had very close mean scores. This result may be related to the fact that women are more likely to be caregivers in each period of life and the majority of women assume the primary responsibility for any illness and care in their family in the society.…”
Section: Discussionmentioning
confidence: 95%
“…V sistematični pregled literature smo vključili 35 znanstvenih prispevkov, ki se nanašajo na področje Evrope (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), Azije (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), Avstralije (29)(30)(31), Severne Amerike (32)(33)(34)(35) in Južne Amerike (36)(37)(38). Skupni povprečni delež žensk v obravnavanih študijah je 57 % .…”
Section: Rezultatiunclassified
“…Pri skupinah z nižjo izobrazbo in pri rasnih in etičnih manjšinah je opazno pomanjkanje informacij in znanja o demenci (4), s tem pa tudi negativen in bolj stigmatizirajoč odnos (5,29). Avtorji raziskav, opravljenih v Združenem kraljestvu, so ugotavljali, da so simptome demence bolje poznali predstavniki bele rase v primerjavi s temnopoltimi (12). V brazilski raziskavi so 2,3-krat večjo stopnjo prisotnosti stigme zaznali pri manj izobraženih osebah v primerjavi z bolje izobraženimi (37).…”
Section: Poznavanje Demence In Stigmaunclassified
“…A recent systematic review and meta-analysis concluded that digital gaming can be as effective as a stand-alone or a multi-component program while appealing to a diverse population regardless of age or gender [10]. A prominent instructional method in the field of nursing education is the use of serious games [12][13][14][15][16][17]. Supporters of digital games also promote the accessibility and convenience of such games [18].…”
Section: Introductionmentioning
confidence: 99%